2017
DOI: 10.3897/zookeys.721.20287
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the species of Lytopylus from Area de Conservación Guanacaste, northwestern Costa Rica (Hymenoptera, Braconidae, Agathidinae)

Abstract: Thirty two new species of Lytopylus (Agathidinae) are described with image plates for each species: Lytopylus alejandromasisi sp. n., Lytopylus alfredomainieri sp. n., Lytopylus anamariamongeae sp. n., Lytopylus angelagonzalezae sp. n., Lytopylus cesarmorai sp. n., Lytopylus eddysanchezi sp. n., Lytopylus eliethcantillanoae sp. n., Lytopylus ericchapmani sp. n., Lytopylus gahyunae sp. n., Lytopylus gisukae sp. n., Lytopylus guillermopereirai sp. n., Lytopylus gustavoindunii sp. n., Lytopylus hartmanguidoi sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…COI data are not always diagnostic. In the revision of Lytopylus (Braconidae, Agathidinae) (Kang et al 2017), two of the 32 reared species from Costa Rica did not achieve a 2% COI divergence, yet they had distinct morphologies and host data. The error rate, if COI had been used exclusively for the Alabagrus and Lytopylus revisions, would be ~ 1%, far better than the grossly underestimated 15% error rate assumed for predominantly morphological revisions of braconids as demonstrated in the database of Yu et al (2016).…”
Section: Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…COI data are not always diagnostic. In the revision of Lytopylus (Braconidae, Agathidinae) (Kang et al 2017), two of the 32 reared species from Costa Rica did not achieve a 2% COI divergence, yet they had distinct morphologies and host data. The error rate, if COI had been used exclusively for the Alabagrus and Lytopylus revisions, would be ~ 1%, far better than the grossly underestimated 15% error rate assumed for predominantly morphological revisions of braconids as demonstrated in the database of Yu et al (2016).…”
Section: Solutionsmentioning
confidence: 99%
“…As a final illustration of how ineffective morphology is to differentiate braconid species, we will paraphrase a report published by Kang et al (2017). Ilgoo Kang (at that time a new graduate student) and Michael Sharkey (with decades of experience in species-level morphological alpha taxonomy) tested their ability to differentiate the species of Lytopylus before including COI and host data.…”
Section: Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent revisions of ichneumonoids in the subfamilies Agathidinae and Microgastrinae have investigated the utility of the DNA barcoding region of the gene cytochrome c oxidase subunit I (COI) for species delimitation, paired with morphological and ecological host-use characters (e.g., Fernandez-Triana et al 2014). Kang et al (2017) created initial molecular operational taxonomic units (MOTUs) for the genus Lytopylus using neighbor joining and maximum likelihood trees, clustering species with boundaries at a sequence divergence of 2%. The MOTUs matched the final species concepts for Lytopylus at 96.6%.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the results, 28S interspecific genetic distances between species were much lower than 16S, indicating confirmation of species boundaries based on 28S sequences would be more difficult. 16S sequences exhibited high interspecific genetic distances but mitochondrial cytochrome c oxidase subunit I (COI) barcodes obtained using universally known markers (Folmer et al 1994;Hebert et al 2004) may be more useful to delimit Neocardiochiles species than 16S as confirmed in many other braconid studies (Smith et al 2008;Smith et al 2012;Fernandez-Triana et al 2014;Kang et al 2017;Fernandez-Triana et al 2019;Meierotto et al 2019; Fagan-Jeffries and Austin 2020; Sharkey et al 2021a, b;Slater-Baker et al 2022). Two single gene trees (See Suppl.…”
Section: Molecular Datamentioning
confidence: 97%